101 Things for Kids to Do Outside - Isaac, Dawn (Kyle Books, 2014)
Packed with games, projects, crafts, experiments and gardening inspiration, 101 Things for Kids to do Outside will have your children racing out to try something new. The huge selection of ideas covers all four seasons and ranges from quick 10-minute activities to a full day of fun. From party games and treasure hunts to simple gardening projects, each idea is simple to follow and illustrated with colour photography, so you can't go wrong! Activities include building a human sundial, creating an outdoor collage, setting up a wormery, planting a potato tower, making natural inks, flying a homemade kite and playing torch tag. This hands-on guide will help children get the most from being outdoors, and you don't need a big garden - a local park or small area will suffice. 101 Things for Kids to do Outside is sure to get your kids away from the computer and provide hours of entertainment for the entire family.